2003
DOI: 10.1046/j.1440-1746.2003.02971.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of choledochal bile in patients with choledocholithiasis admitted to a tertiary hospital

Abstract: E. coli, K. pneumoniae, E. faecalis and Streptoccocus sp. were the most common bacteria isolated in the bile of patients with cholangitis and choledocholithiasis, which were sensitive to a simple therapeutic regimen, such as the combination of ampicilin and gentamicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 17 publications
(18 reference statements)
5
27
0
6
Order By: Relevance
“…In our study, in 64.2% of cases we found gram-positive bacteria, in 22.2% gram-negative bacteria, and in 13.5% Candida. Most common isolates were Enterococcus species, whereas, in the non-transplant setting, more gram-negative bacteria, especially E. coli and klebsiella, are found [18][19][20][21]. Our results confirm former studies that showed a shift in microbial spectrum in bile of immunosuppressed patients after LT towards gram-positive bacteria with a markedly increased incidence of Enterococci [8][9][10].…”
Section: Discussionsupporting
confidence: 86%
“…In our study, in 64.2% of cases we found gram-positive bacteria, in 22.2% gram-negative bacteria, and in 13.5% Candida. Most common isolates were Enterococcus species, whereas, in the non-transplant setting, more gram-negative bacteria, especially E. coli and klebsiella, are found [18][19][20][21]. Our results confirm former studies that showed a shift in microbial spectrum in bile of immunosuppressed patients after LT towards gram-positive bacteria with a markedly increased incidence of Enterococci [8][9][10].…”
Section: Discussionsupporting
confidence: 86%
“…However, E. faecalis is one of the most common lactic acid bacteria found in the GIT (12) and one of the predominant microbial species isolated from drainage devices used in biliary surgery (33). E. faecalis has also been isolated directly from the gallbladder (15). This indicates an inherent ability to tolerate high concentrations of bile under in vivo conditions.…”
mentioning
confidence: 99%
“…In a study by Capoor et al (2008), (9) most common organism was isolated was E. coli followed by Klebsiella pneumonia, Citrobacterfreundii and Salmonella. A number of other authors (Bhansali et al in 1985, (10) Cristina et al in 2003 (11) and Fazal et al in 2014) have reported E Coli to be the most common organism isolated from bile. The reason for E. Coli being the commonest bacteria in bile is because it is the commonest bacteria found in GIT and infection to biliary system comes from the GIT.…”
Section: Discussionmentioning
confidence: 94%
“…(10) Cristina et al reported that all gram negative organisms were sensitive to gentamicin. (11) Fazal et al reported high sensitivity of E. Coli to cefuroxime and ceftriaxone and showed high resistance to amoxicillin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%